2017
DOI: 10.31004/jn.v1i1.94
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Dan Sikap Petani Terhadap Pengggunaan Alat Pelindung Diri (Apd) Di Rw 01/03 Desa Sialang Panjang Kecamatan Tembilahan Hulu Tahun 2016

Abstract: Alat Pelindung Diri (APD) merupakan salah satu upaya untuk melindungi sebagian atau seluruh tubuhnya dari adanya potensi bahaya kecelakaan kerja dan penyakit akibat kerja. Penggunaan APD sangat diperlukan untuk melindungi pekerja dari bahaya zat kimia yang digunakan petani yang mengandung pestisida. Penggunaan APD yang tepat akan melindungi petani dari paparan konsentrasi tinggi yaitu dengan menggunakan masker yang berguna melindungi petani dari debu atau partikel – partikel yang lebih kasar akan masuk kesalur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…4 shows a significant relationship at the 5% significance level, in that case, the three components (knowledge, attitudes, and actions) simultaneously influence shallot farmers to equip PPE in spraying insecticides. The results of this study are to the findings of Indrawati (2017), that knowledge and attitudes have a significant relationship with the use of PPE among farmers in Sialang Panjang Village, Tembilahan Hulu District. However, it is different from the findings of Aeni et al (2018) that there is no relationship between knowledge and attitudes regarding the practice of using PPE among farmers who use pesticides in Sigambir Village, Brebes District and the findings of Rachman et al ( 2020) at PT.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…4 shows a significant relationship at the 5% significance level, in that case, the three components (knowledge, attitudes, and actions) simultaneously influence shallot farmers to equip PPE in spraying insecticides. The results of this study are to the findings of Indrawati (2017), that knowledge and attitudes have a significant relationship with the use of PPE among farmers in Sialang Panjang Village, Tembilahan Hulu District. However, it is different from the findings of Aeni et al (2018) that there is no relationship between knowledge and attitudes regarding the practice of using PPE among farmers who use pesticides in Sigambir Village, Brebes District and the findings of Rachman et al ( 2020) at PT.…”
Section: Resultssupporting
confidence: 73%
“…The level of community education has a positive effect on community behavior in land management (Suwarno et al, 2014). The results showed that nonformal education includes factors that influence the attitude of farmers in Sukoharjo Regency (Ayu A et al, 2020), knowledge also has a significant relationship with the attitude of farmers towards the use of Personal Protective Equipment (PPE) in Sialang Panjang Village, Tembilahan Hulu District (Indrawati, 2017), knowledge has a significant relationship with the use of PPE in spraying workers at PT. RKK Mekar Sari Village, Kumpeh District, Muaro Jambi Regency (Entianopa et al, 2016), significant relationships between knowledge, attitudes, and availability of PPE with the behavior of the use of PPE are also found in pesticide spray farmers at the Paal Merah II Puskesmas Post in 2021 (Hasanah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This research was in line with a study conducted by (Dinaediana, 2017), which states that most citrus farmers in Dadok Nagari Koto Tinggi River have low knowledge about the use of PPE (65.7%).Most respondents had a negative attitude about the use of PPE (61.4%), there is a relationship of comfort (p<0.001), knowledge (p= 0.028) and attitude (p<0.001) to the use of PPE. There is a significant relationship between knowledge and attitude towards PPE in farmers in Sialang Panjang Village, Tembilan Hulu Subdistrict (Indrawati, 2017).…”
Section: Discussionmentioning
confidence: 99%